Online social networks for prevention and promotion of oral health: a systematic review - de Oliveira Júnior, Alcir J; Oliveira, Julicristie M; Bretz, Yasmin Pm; Mialhe, Fábio L (Canadian Journal of Dental Hygiene, 2023)
To evaluate the impact of online social networks (OSN) as resources for promoting behaviour changes related to the prevention and promotion of oral health. This was a systematic review with meta-analysis of randomized clinical trials identified in databases (MEDLINE/Embase/Lilacs), published up until May 2022, and prepared according to Cochrane recommendations. Studies that used OSN (WhatsApp , Telegram , TikTok , Facebook , Twitter , YouTube , Instagram , Soundcloud , Flickr , LinkedIn , and Webradio ) were included. The protocol was registered in the International Prospective Register of Systematic Reviews (CRD42021248045). In total, 3171 studies were evaluated, of which 12 studies met the inclusion criteria for the review and contained data on 1669 participants. The most frequently investigated OSN were WhatsApp , followed by Telegram , and YouTube . All studies included were at high risk of bias. Data extraction allowed the meta-analysis of gingival index (GI) and oral health knowledge (OHK) outcomes for young people. Findings revealed that young people exposed to digital interventions via OSN showed a reduction in GI when compared with traditional educational interventions. This reduction occurred in all young people (standardized mean difference, -0.48; 95% CI, -0.75 to -0.21; = 0.0006, I = 0%; very low certainty), including those who were undergoing orthodontic treatment (standardized mean difference, -0.58; 95% CI, -0.92 to -0.24; = 0.0008, I = 0%; very low certainty). Furthermore, young people undergoing orthodontic treatment and exposed to OSN showed an increase in OHK when compared with participation in traditional educational interventions (standardized mean difference, +0.86; 95% CI, +0.46 to +1.26; < 0.0001, I = 0%; very low certainty). OSN could be effective tools for improving oral health outcomes in young people.